Plan, Repair, Execute, Explain — How Planning Helps to Assemble your Home Theater - Bercher, Pascal; Biundo, Susanne; Geier, Thomas; Hoernle, Thilo; Nothdurft, Florian; Richter, Felix; Schattenberg, Bernd (Proceedings of the International Conference on Automated Planning and Scheduling, 2014)
In various social, work-related, or educational contexts, an increasing demand for intelligent assistance systems can be observed. In this paper, we present a domain-independent approach that combines a number of planning and interaction components to realize advanced user assistance. Based on a hybrid planning formalism, the components provide facilities including the generation, execution, and repair as well as the presentation and explanation of plans. We demonstrate the feasibility of our approach by means of a system that aims to assist users in the assembly of their home theater. An empirical evaluation shows the benefit of such a supportive system, in particular for persons with a lack of domain expertise.